Relaciones de la familia y del hijo/a con superdotación intelectual - Valadez Sierra, María De Los Dolores; Gómez Pérez, Mª Ángela (FAISCA: Journal of High Abilities, 2011)
In this study we try to apply the theoretical model of the school of Milan, which indicates that families activate tools of self-correction, as part of a system where so that the child diagnosed in this case as gifted, does not cause a negative imbalance in the family, but that is an evolutionary change in the family system. Therefore this study aims to know the relations between the child with intellectual giftedness. The sample consisted of pupils of primary, 120 first and 145 second grade, for a total of 265. Progressive Matrices of Raven, colored scale Test y the WISC-R intelligence scale were applied in order to select the children who obtained the gifted criterion , it is, a 130 points IQ; 13 children covered this criterion. Within the conclusions we highlight that parents claim that they have differences and arguments inside his home, but that they dialogue always to reach an agreement and to take decisions for the benefit of the child’s needs. It is demonstrated from the systemic model that gifted children do not cause a negative imbalance in the family, but they cause an evolutionary change in the family system.